STUDI GEOLOGI DENGAN KAJIAN KONDISI HIDROGEOLOGI DI KECAMATAN AIRMADIDI, KABUPATEN MINAHASA UTARA, PROVINSI SULAWESI UTARA - Kaunang, J. J.; Momongan, A. J.; Budiharso, A. S. (Journal Geological Processes, Risks, and Integrated Spatial Modeling, 2023)
Groundwater is water content that accumulates in rock strata below the surface. Ground water is stored in the gaps between rock grains and cracks in the rock layer which will then be called an aquifer. The water contentstored and transported by spaces between grains, rock cavities, and cracks in rock. Groundwater can flow either vertically or lateral depending on the morphological, hydrological and geological conditions. The aim of this research is to determine the condition geology in Airmadidi District, North Minahasa Regency, North Sulawesi Province, and knowing the hydrogeological conditions. This research was carried out using qualitative analysis methods to determine geological and hydrogeological conditions. Using data from literature studies, analysis of each aspect, and observations in the field. From this research, 3 units were found lithology, namely the Tondano Pyroclastic unit, the Mount Klabat Pyroclastic unit, and the Mount Klabat Lava Flow unit, based on data It was concluded that the hydrogeological conditions in Airmadidi District, North Minahasa Regency, North Sulawesi Province using a tentative model to visualize subsurface conditions that have high groundwater productivity.